ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI INDONESIA - Yoghi Citra Pratama (Faculty of Economic and Business, 2014)
The purpose of this study is to determine the factors that affect poverty in Indonesia. The method used in this study is a multi-linear regression, which is an analysis tool that is used to see the effect of the independent variables which are, the level of income per capita, the rate of inflation, the level of household consumption, level of education, human development index (HDI) and the poverty level as dependen variable. The data used in this study is secondary data of 33 provinces in Indonesia in 2012. From the study it can be concluded that the variable income per capita, inflation, education level human development index (HDI) and consumption simultaneously affects variable rate of poverty, it can be seen from the test that showing the level signifkansi f <0.05. And from R square is known that the independent variable can explain the poverty rate by 56 percent and the remaining 44 percent would be explained by other variables whose not examined in this studyDOI: 10.15408/ess.v4i1.1966